Citation and Dynamics of Scientific Communication - López-López, Wilson; Pontificia Universidad Javeriana (2010)
In the last few years, citation has become a crucial element in the assessment of academic production. Nevertheless, in the Latin American context, citation has given rise to several questions for researchers, especially those in the Social Sciences and Humanities fields: First, is it possible to do research without communicating it? Is communication a necessary condition in the dynamics of research? This is, does anybody read what we publish? Second, who reads and uses what we publish? What are the social responsibility implications of researchers who do not publish what they write? Should researchers understand the dynamics of international communication as part of their work? Can researchers just ignore that what they publish has an influence on readers? What is the epistemological perspective involved in that Social Science researchers question themselves about scientific communication? It is clear that these questions are already answered for editors. Their academic work is an exercise in communication, and their concerns are not just to account for content quality, but for the communicational implications of this content. For an editor, in sum, unpublished research does not exist. Hence, communication is a necessary element of the research process, and it is important to seek that what is published is also read and used when possible. Communication of research and academic production is an act of social responsibility, not only from the academic or economic perspectives. This responsibility is shared by editors and researchers, and the latter should be acquainted with networks of academic peers and potential users of the knowledge they create. Researchers should therefore think locally, regionally and globally, and they must take responsibility for the consequences of what they publish. The epistemology involved may be linked to different philosophical perspectives that share that research is impossible without communication. It is also clear that research communication has multiple forms of expression which include academic and research journals (that publish peerreviewed research results), but also general journal articles or communication media such as booklets, videos, audios, etc., which are directed towards non-academic audiences. Surely, some of these research results may in turn create other products (patents, interventions, psychosocial accompaniments, other technical or technological artifacts, criticism, reports, policy suggestions, education processes or consulting services). Nevertheless, valuing of academicians is important and it is associated to peer-reviewers, who are part of the assessment of research, projects, articles or knowledge appropriation. Citations are of transcendental importance for researchers, academicians, editors and academic policy managers in this last item. It is clear that citations have complex analysis systems transcending the old impact factor. An academic research journal has no other option than to pursue the implementation of strategies devised to increase communication, visibility and citation of academic production. Wilson López López Editor